(untitled) (City: History, Culture, Society, 2026)
The article examines the National Expocenter of Ukraine (VDNH) in Kyiv as a space of materialized utopia and as an instrument of Soviet ideological representation. It traces the formation of the complex from its postwar design to its contemporary transformations, with particular attention to the architecture of the ensemble, its relationship to political processes in the USSR, and the role of the Exhibition as a mechanism for visualizing a desired future. It demonstrates that VDNH functioned as a symbolic space intended to sustain belief in the utopian socialist project while concealing the realities that contradicted it. Special attention is given to the post-Soviet period, the decline of the complex, its gradual revitalization after 2016, and the tensions between the commercialization of space and the need to preserve cultural heritage. The article analyzes artistic projects by contemporary Ukrainian artists realized on the territory of VDNH as forms of critical reinterpretation of Soviet heritage, practices of memory work, and decolonial approaches. It argues that these artistic interventions reveal VDNH not merely as a propagandistic architectural ensemble, but as a multilayered heritage site that requires study and preservation.